Scrutinizing Grammatical Challenges within Indonesian-developed Mobile Game: ‘Code Atma’ - Erina Andriani (LET: Linguistics, Literature and English Teaching Journal, 2022)
The use of another language can cause barriers to transferring ideas from one language to another, such as grammatical challenges. It happens when the structures for delivering information are different within languages. Grammatical challenges can also occur for Indonesian EFL users. To combat this, various media are continuously developed to assist with language learning and give exposure to the English language in use. Games are an example of excellent learning sources that provide texts, descriptions, and stories. However, games might not be developed by natives and could potentially contain errors. Yet, previous research rarely conducted grammatical error analysis on games. Therefore, this study aimed to investigate the grammatical challenges within the Code Atma game. This study used document analysis to evaluate the grammatical accuracy of the passages in Code Atma. The findings showed that there were 630 grammatical errors, with verb errors accounting for the highest percentage and incomplete sentences for the lowest. is-selection was the type with the highest number of errors, while blends were the lowest. The implications of this study are the improvement of the game’s grammatical aspect, the use of games as EFL learning sources, and the identification of grammatical errors using error analysis.